2016
DOI: 10.1002/aqc.2698
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of the endangered thick‐shelled river mussel (Unio crassus) near the northern limit of its natural range

Abstract: 1. The thick-shelled river mussel, Unio crassus (Bivalvia: Unionoida), is one of Europe's most-threatened mussels. Finnish populations of U. crassus lie close to the northern limit of its natural distribution. Extirpation of these populations will reduce the range of this endangered species.2. Growth characteristics of U. crassus were measured in a river running through the Helsinki metropolitan area. Shell dimensions (size-at-age data) and annual shell growth increments were used to reconstruct growth rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The unionoid thick‐shelled river mussel Unio crassus occurs in soft substratum and sand‐ and gravel‐rich middle watercourses of varying hydrology (Björk, ; Lopes‐Lima et al, ; Stoeckl & Geist, ) where it averages about 8 to 50 years and a maximum life‐span up to 90 years over its distribution area (Helama, Valovirta, & Nielsen, ; Hochwald, ; Lundberg & von Proschwitz, ). The mussel spawns in late spring, and parasitizes on fish species such as minnow Phoxinus phoxinus , bullhead Cottus gobio and chub Squalius cephalus for about 1 month from late spring to early summer (Hochwald, ; Lundberg, Bergengren, & von Proschwitz, ; Maaß, ; Taeubert, Gum, & Geist, ; Taeubert, Martinez, Gum, & Geist, ).…”
Section: Introductionmentioning
confidence: 99%
“…The unionoid thick‐shelled river mussel Unio crassus occurs in soft substratum and sand‐ and gravel‐rich middle watercourses of varying hydrology (Björk, ; Lopes‐Lima et al, ; Stoeckl & Geist, ) where it averages about 8 to 50 years and a maximum life‐span up to 90 years over its distribution area (Helama, Valovirta, & Nielsen, ; Hochwald, ; Lundberg & von Proschwitz, ). The mussel spawns in late spring, and parasitizes on fish species such as minnow Phoxinus phoxinus , bullhead Cottus gobio and chub Squalius cephalus for about 1 month from late spring to early summer (Hochwald, ; Lundberg, Bergengren, & von Proschwitz, ; Maaß, ; Taeubert, Gum, & Geist, ; Taeubert, Martinez, Gum, & Geist, ).…”
Section: Introductionmentioning
confidence: 99%
“…The shell measurements and population dynamics of U. crassus are related to the water conditions and the region [10,[29][30]. In studies on U. crassus, the maximum shell length was reported as 66.9 mm in the Wkra River (Poland) [31]), 67.4 mm in the Palakaria River (Bulgaria) [32], 81 mm in Bohemia (Czech Republic) [30], 83 mm in Estonia [9], 85.4 mm in the Vantaa River (Finland) [33], and 95 mm in the Susa River (Denmark) [34]. During this study, which was done in Çine Creek, the largest length was measured as 92.50 mm, while another study conducted in Sapanca Lake on the west coast of Turkey reported that U. crassus were found with lengths of 74 mm [35].…”
Section: Discussionmentioning
confidence: 99%
“…When all these studies are taken into consideration, it is seen that the mussel measured in Çine Creek has the longest length except for the Susa River. Helama et al [33] reported that the average age of death for U. crassus individuals in the Vantana River (Finland) was 12.5 years and the longest living individual has a lifespan of 38 years, and that these individuals weighed 58.7 mm on average and weighed 14.9 g on average. The largest individual measured 85.4 mm and weighed 44.4 g and this individual was 15 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mussel with flat and transparent gills was categorized as non-gravid, including male individuals. The individual shell length (nearest mm, Helama et al 2017) was noted. The ratio of gravid/non-gravid mussels was calculated for every sampling occasion.…”
Section: Mussel Investigationsmentioning
confidence: 99%